Impact of Helminth Infections on Female Reproductive Health and Associated Diseases - Chetty, Alisha; Omondi, Millicent A.; Butters, Claire; Smith, Katherine Ann; Katawa, Gnatoulma; Ritter, Manuel; Layland, Laura; Horsnell, William (Frontiers in Immunology, 2020)
A growing body of knowledge exists on the influence of helminth infections on allergies and unrelated infections in the lung and gastrointestinal (GI) mucosa. However, the bystander effects of helminth infections on the female genital mucosa and reproductive health is understudied but important considering the high prevalence of helminth exposure and sexually transmitted infections in low- and middle-income countries (LMICs). In this review, we explore current knowledge about the direct and systemic effects of helminth infections on unrelated diseases. We summarize host disease-controlling immunity of important sexually transmitted infections and introduce the limited knowledge of how helminths infections directly cause pathology to female reproductive tract (FRT), alter susceptibility to sexually transmitted infections and reproduction. We also review work by others on type 2 immunity in the FRT and hypothesize how these insights may guide future work to help understand how helminths alter FRT health.